PENERAPAN MODEL PEMBELAJARAN BERDASARKAN MASALAH (PBM) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA SISWA KELAS IIIB SD NEGERI 117 PEKANBARU - Destika Irma; Syahrilfuddin '; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract. This research is motivated by the low value of math students in class IIIB in 117 SD Negeri Pekanbaru, because the old model is not match to learn math because it is an exact science and discovery. Based on these problems, it is necessary given way to solve the problem include applying Problem Based Learning (PBM) model. This model is accordance with the enviromental condition of the student role in their daily lives that connected to mathematics, and give a chance to student to solve the problem. Subjects in this research were 21 students of class IIIB of 117 SD Negeri Pekanbaru. This research was conducted in two cycles, by doing the daily test of the end of each cycle. The result of this research shows that the problem based learning (PBM) model can increase math studies, completeness math learning outcomes 66,67 in first cycle is 80, then in second cycle increased to 95. The analys data of student activity was good too, in first cycle is 70% and in second cycle increase to 90%. And last, the analys data of teacher activity in first cycle is 80% and increase to 95% in second cycle. Based on this result shosw that problem based learning (PBM) model can increase math studies the students of class IIIB in 117 SD Negeri Pekanbaru.Keywords : Problem Based Learning (PBM), Mathematics Learning Outcomes..